Wokół pisarstwa Andrzeja Walickiego. - Sobczak, Jan (Acta Polono-Ruthenica, 2009)
The basis of the authors deliberations is the collection of articles written by the students and supporters of professor Andrzej Walicki ideas who is considered to be the best Polish slavist and who is widely known abroad. The collection of articles About Andrzej Walicki. Almanach of Russian thoughts was published under the auspices of Warsaw University and edited by Janusz Dobieszew- ski, Jan Skoczyñski, and Micha³ Bihun who are interested in Russian philosophical thoughts in this area and who have considerable achievements in this sphere. The author claims that people who deal with and are interested in Russia, its history, culture and especially historio-philosophical thoughts, should be familiar with the articles published in this collection. It should be underlined that in Walickis interests and scientific research and as well in the writings of this advocate of Russian thoughts, Russian dominant is very clear and Jan Sobczak undertook the reconstruction of his views on stalinism and roots of Russian totalitarism, on the origins of Russian bolshevism. Moreover, Jan Sobczak pointed that Walickis ideas and thoughts are present in the contemporary Polish discourse on the subject of not only Polish Russian connections but also the assessment of PRL and abusing such concepts as communists postcomunists, etc. or assessment of martial law, an attitude to Solidar- noæ, etc. Walickis perception of Polish position in Europe depicts his characteristic statement: Poland stands a better chance as west of east than periphery of west. [...] Russians are the only nation for which polish culture is significant, where the name of Mickiewicz is widely known. It is our cultural, spiritual capital that should be care for. Since 1956 Polish system has been far away from standards of totalitarianism. In fact, that time Poland has become distant from the totalitarian model. Walicki has always criticized Polish foreign politics when it started to be defeated by different nationalist phobias.